(3jJjeI GdOgQ aj eMGSf Cgd GdYUQs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3JQGLe TYQGA GdOhdI GdOjdejI hChdg YVO GdOhdg CHh TLGY afGNSQh Hf Qcf GdOhdI s
(3BNQgG (B:s
(3JQLeI GdTQja CHj GdMSf GHf GdehShi GdfbjH hBNQ eG ajgG ef bUjOI ai HgGA GdOhdg CHj fUQ (B: (3haNQ GdaJi HGdShd dGjfTOg hjQhi adGf eQI hadGf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(9755) s
Keywords: (3GdCOHs